Recent Progress in Near‐Field Tip Enhancement: Principles and Applications. Issue 4 (3rd April 2022) - Yin, Hailong; Zhang, Jianwei; Wang, Xuewen; Cui, Jianlei; Wang, Wenjun; Mei, Xuesong
Abstract : To meet the challenges raised by the fabrication of nanoelectronic devices on currently available micro/nano technologies, article number 2100456 by Jianlei Cui and colleagues reviews the essential principles and recent applications of near‐field tip enhancement induced by laser‐irradiated scanning probe microscope probe tips. Such key applications include nanofabrication, nano‐joining, and nanomanipulation, which are expected to serve a critical role in the fabrication of nanoelectronic devices.